Evidence for the southernmost pre-industrial human expansion on Isla Hornos (Isla Lököshpi), Chile. (October 2022) - Buma, Brian; Morello, Flavia; Rodriguez, Karina; Fillol, Alberto Serrano
Abstract: Abstract : The authors provide an initial report on possibly the southernmost expansion of humans in pre-industrial times. The archaeological site, in the Cape Horn archipelago, consists of a campfire site, fragments of a weapon, and butchered bones. Radiocarbon dating places the site c . 260–460 years BP.